Design of Air Ventilation System for Cargo Hold Vessels Using Solar Desiccant - Alam Baheramsyah; Taufik Fajar Nugroho; Prasetyo Adi Wibowo (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2017)
One of the facilities and infrastructure of the vessel is the ventilation system in the cargo hold to maintain the quality. One attempt to avoid high moisture ratios is to provide a dry air supply by using desiccants. The purpose of this thesis is to design the system of air ventilation with solar desiccant by analysis the calculation with decrease air humidity ratio after passing desiccant rotor as well as fulfillment needs of heater and cooling system using heat of exhaust gas and seawater as well as fulfillment of electricity need using solar energy. From the result of analysis obtain to provide air supply in the cargo hold of 437.5 m3 / hour, the specification of rotor desiccant has a diameter of 550 mm with thickness 200 mm to decrease ratio of outside air humidity equal to 83.1% become 46.5%. Dehumidification air temperature of 47.7oC will be lowered to 35oC by using the sea water cooling media. As for the reactivation air heater requirement of 24.292 kW would be to fulfilled by utilizing the exhaust power of 498.12 kW. And for the electric power needs of the syetm is 34,488 wp will be supplied from the total solar module is 33 units with 345 wp per-capacity.